“Não aparece no raio-x”: cosmologias e práticas de autoatenção no contexto de intermedicalidade na saúde dos Mbya-Guarani em São Miguel das Missões-RS - Sanchez, Karina Lilith Moreira (2021)
This thesis assembles the ethnographic performance held with the Tekoa Ko’enju community, in São Miguel das Missões, Rio Grande do Sul, Brazil. The research falls within the scope of Health Anthropology, Indigenous Health Policy, and Indigenous Ethnology, aiming to comprehend how the Mbya-Guarani self-care practices are related to the contact zone between health professionals and the Mbya and its traditions. To this end, I propose a theoretical approach through the concepts of intermedicality and self-care practices, to put together these initiatives to build differentiated attention towards indigenous health. Thus, this project investigates the different universes of meaning in this context, discussing the concepts of health, attention, disease. Moreover, there is a pursue to understand the notion of body/person as a substrate for examining intermedicality, especially on the negotiations that the community establishes with non-indigenous agents. Therefore, the Nhe’eis approached as the notion of spirit that initiates the production of healthy Mbya bodies. It is argued that this conception is formulated through ideals of behavior that, consecutively, are guided by a Guarani way of being (Nhandereko), which inevitably dialogues with the contemporary disguises of imperialism. Faced with these ideas, the self-care practices of local therapy are analyzed, providing an overview of the intersection between biomedicine and religion. Finally, I display how the imperial context translates itself into austerity policies for the First people, during the world’s worst health crisis in modern times.